2011
DOI: 10.1073/pnas.1014339108
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus rtxA1 gene recombination generates toxin variants with altered potency during intestinal infection

Abstract: Vibrio vulnificus is a food-borne bacterial pathogen associated with 1% of all food-related deaths, predominantly because of consumption of contaminated seafood. The ability of V. vulnificus to cause disease is linked to the production of a large cytotoxin called the "multifunctional-autoprocessing RTX" (MARTX Vv ) toxin, a factor shown here to be an important virulence factor by the intragastric route of infection in mice. In this study, we examined genetic variation of the rtxA1 gene that encodes MARTX Vv in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
143
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 29 publications
3
143
0
Order By: Relevance
“…An exception may be the toxin, which several studies have recently shown to be essential to virulence in mouse models (57,58,59,60,61).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…An exception may be the toxin, which several studies have recently shown to be essential to virulence in mouse models (57,58,59,60,61).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…1) (19,21,22). This 376-aminoacid domain shares homology with internal domains of other large bacterial toxins, including Photorhabdus Makes Caterpillar Floppy toxins Mcf1 and Mcf2 and Pseudomonas fluorescens FitD toxin (24,25).…”
mentioning
confidence: 99%
“…Among the eight potential effector domains carried by MARTX Vv toxins of various isolates (21)(22)(23), a ubiquitous effector domain carried by all clinical biotype 1 V. vulnificus strains and by biotype 2 strains that infect eels is the Makes Caterpillars Floppy-like (MCF Vv ) domain ( Fig. 1) (19,21,22).…”
mentioning
confidence: 99%
“…However, a potential limitation for the application of antiserum against VvPS as a protective agent would be the existence of a large number of serotypes and carbotypes of VvPS, which could limit the cross-reactivity of anti-VvPS serum (45,59,60). The use of MAbs against RtxA1-C, the C-terminal region of V. vulnificus RtxA1/MARTX Vv , could avoid this potential concern because the C-terminal region of V. vulnificus RtxA1/MARTX Vv is highly conserved (12,14,15,41). In support of this, three therapeutic MAbs (21RA, 24RA, and 47RA) against the V. vulnificus M06-24/O strain recognized both intact and processed RtxA1/MARTX Vv products in different clinical and environmental strains (ATCC 29307, CMCP6, YJ016, and Evn1) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the culture supernatants of CMCP6 and YJ016, an additional band with an apparent molecular mass of 170 kDa was also recognized by the three MAbs, presumably due to toxin variants with different arrangements of effector domains generated by V. vulnificus rtxA1 gene recombination (Fig. 5A) (41). Consistent with the data obtained with the three cross-reactive MAbs, RtxA1-C-specific antiserum detected the intact RtxA1/MARTX Vv protein (ϳ500 kDa) and the smaller bands (ϳ130 and/or ϳ170 kDa) from all strains tested, indicating that these smaller bands could be cleavage products of the intact RtxA1/MARTX Vv protein ( Fig.…”
Section: Fr-i Fr-i-ii Fr-i-ii-iii % Of Surviving Micementioning
confidence: 99%